(untitled) (Educational Dimension, 2024)
Over the past few years, smartphones have grown exponentially in popularity, especially in education. As part of a new pedagogical trend, many educational institutions are integrating smartphones into the classroom as a learning tool. This paper investigates students’ different use of smartphones during lessons, both with and without their teacher’s permission. The study also examines the duration of smartphone use by students in these two cases. A quantitative research design was employed, and data from a random sample of 195 students in the Setif district (east of Algeria) was collected using a questionnaire. The data was analyzed using descriptive statistics in SPSS v26. The findings revealed that 97.4% of students own a smartphone, and 77% use it daily for more than three hours. Only 27.2% of teachers allow their students to use smartphones during lessons. The findings also indicated that 60% of learners spent more than 10 minutes using their smartphones during lessons without the teacher’s permission for non-educational purposes. Additionally, 23% of learners spent more than 10 minutes using their smartphones during lessons with the teacher’s permission for educational purposes. The study concluded that there is a link between the amount of time learners spend on their smartphones in classrooms and teacher decisions. Learners use their smartphones more for non-educational purposes if the teacher does not allow them to use them for educational purposes. The most important recommendation is to understand how students use and think about their smartphones.